Resveratrol plus low-dose hydroxyurea compared to high-dose hydroxyurea alone is more effective in γ-globin gene expression and ROS reduction in K562 cells. Issue 6 (19th March 2023) - Alipour, Maedeh; Nasiri, Nahid; Kazemi, Fariba; Zare, Farahnaz; Sharifzadeh, Sedigheh
Abstract: Hydroxyurea (HU) is an anti-cancer drug that is used for the treatment of hemoglobinopathies as a γ-globin inducer. However, its dose-dependent effects have hampered its clinical reliability. Resveratrol (RSV) is an antioxidant and γ -globin inducer. The present study aimed to assess their combined effects on the γ-globin gene expression and reactive oxygen species (ROS) level of K562 cells. The results indicated that the γ-globin gene expression was approximately two folds higher in the group treated with RSV 50 µM + HU 25 µM in comparison to HU 100 μM alone (*** p < 0.001). However, there was an inverse relationship between the expression of γ-globin gene and HU concentration in the combined groups. Furthermore, the combinations of RSV and HU significantly reduced ROS levels compared to single drugs. Overall, the combination of these compounds was an appropriate strategy for increasing γ-globin expression, reducing oxidant levels, and alleviating the adverse effects of HU. Graphical Abstract: UF0001